Service quality as an antecedent in enhancing customers’ behavioural intentions: a case study of Malaysian army medical centers - Azman Ismail,; Ilyani Ranlan Rose,; Nur Afiqah Foboy, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Behavioural intention is a customer preference to use services provided by service providers and this preference manifests itself in the form of the customer’s readiness to recommend, intention to repurchase, and deliver positive words of mouth regarding the services provided. This has a lot to do with the ability of providers to effectively offer services which are not only tangible but also reliable, responsive, reassuring, and empathic. Extant studies in this field reveal that the ability of service providers to appropriately deliver these qualities in performing daily job may have a significant impact on customers’ behavioural intentions. Even though this relationship has been studied widely the role of service quality as an important antecedent has been relatively ignored in current organizational quality research literature. In this light, this study was undertaken to measure the relationship between service quality and behavioural intention. Primary data were gathered from 128 customers and eleven administrative staff and doctors of the military hospitals in Peninsular Malaysia. The outcome of a SmartPLS path model analysis confirmed that the ability of organizations to properly implement quality in medical services would enhance the intention of customers to continuously use the services.